On a measure of integral square deviation with generalized weight for the Rosenblatt–Parzen probability density estimator - Babilua, P.; Nadaraya, E.; Sokhadze, G. A. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
The limit distribution of an integral square deviation with weight in the form of “delta”-functions for the Rosenblatt–Parzen probability density estimator is determined. In addition, the limit power of the goodness-of-fit test constructed by using this deviation is investigated.